Innovative machine learning for drilling fluid density prediction: a novel central force search-adaptive XGBoost in HPHT environments - Shanmugasundar, G.; Manjunatha, R.; Cep, Robert; Logesh, K.; Kaushik, Vikas; Raju, S. Srinadh; Elangovan, Muniyandy (Frontiers in Energy Research, 2024)
Oil and gas industries are having a special dilemma when it comes to High Pressure, High Temperature (HPHT) drilling as the accuracy forecasting of the drilling fluid density (DFD) is a vital factor for safe and efficient operations. Complicated relationships and inconsistencies in HPHT situations are rarely mapped by current forecasting models while their buggy performance and safety risks during drilling can be underestimated. In this research, we propose a novel machine learning (ML) approach to enhance the accuracy of DFD anticipation under HPHT conditions: Central Force Search-adaptive extreme Gradient Boosting (CFS-XGB). The paper uses a dataset that has drilling variables together with the DFD for HPHT situations to examine the accuracy of the CFS-XGB model. Excluding the abnormalities of data or mistakes, the reliability of the original data is maintained by applying min-max normalization. After that, finding the important features with the help of the boosted principal component analysis (BPCA) approach to the normalized data will make the CFS-XGB methodology's prediction efficacy to ensure a major improvement. This research is experimented in Python platform and the performance of the proposed CFS-XGB method is analyzed in terms of MSE, R 2 and AAPRE metrics. The suggested approach performs better than the current methods in forecasting drilling fluid concentration in HPHT settings, according to the experimental data. This development in predictive modelling helps to increase the productivity and safety of drilling operations, which eventually helps the oil and gas sector manage the challenges posed by HPHT drilling settings.